Hierarchically porous 2D carbon from bio-waste: a sustainable, rapid, and efficient oxidase mimic for the colorimetric detection of ascorbic acid - Verma, Chandra Jeet; Singh, Priya; Ojha, Ravi Prakash; Prakash, Rajiv (Royal Society of Chemistry, 2022)
In the present work, a porous 2D carbon-based sustainable, rapid, and efficient oxidase mimic for ascorbic acid (A.A.) detection has been discussed. Here, Eichhornia crassipes (water hyacinth) biomass waste was used as a precursor, which resulted in advanced N, O-doped hierarchically porous 2D carbon. In this, the heteroatom-like N, O are well-dispersed while 2D carbon has a high surface area. For this, a one-step carbonizing technique was used in an inert environment without any surfactant/activating chemical aid. The structural parameters of such a 2D carbon material were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, and X-ray photoluminescence spectroscopic techniques. The morphological investigations of 2D carbon were done by field emission scanning electron microscopy and transmission electron microscopy. Nanozymes, also called nanomaterials having the behaviors of enzymes, are promising materials for biomedical fields. Due to the absence of corrosive H2O2 in the reaction path, oxidase-like nanozymes are gaining more importance and attention. Due to the high surface area and N, O-doped hierarchical pores, the 2D carbon possessed more catalytic active sites and facilitated rapid oxidase-like activity for the chromogenic substrate 3,3′,5,5′-tetramethylbenzidine (TMB). The oxidation culminated in a charge-transfer product with an absorbance peak at 652 nm. Ascorbic acid is a biomolecules that displays concentration-dependent inhibition property over the oxidase activity of a nanozyme. We developed a colorimetric technique based on a 2D carbon oxidase nanozyme for A.A. sensing. Based on this principle, the presented colorimetric method showed an excellent linearity range from 1 to 70 μM with a 0.26 μM detection limit and the fastest A.A. detection among the other reported colorimetric methods. This work demonstrates a simple approach for preparing a complete metal-free and efficient nanozyme, and explored its use for A.A. detection in orange, lemon, grapes, and human serum. Also, it presents a new avenue to design a sustainable mimetic substrate and further a road map for transforming biowastes into new technology.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: bio-waste; colorimetric detection; ascorbic acid; porous 2D carbon; infrared spectroscopy; X-ray diffraction; X-ray photoluminescence spectroscopic; electron microscopy; Nanozymes; chromogenic substrate; tetramethylbenzidine